Multivariate analysis of vegetative growth and productivity in cultivars of the Cavendish subgroup of the banana - Ricardo Firetti; Adriana Novais Martins; Eduardo Suguino; Patrícia Helena Nogueira Turco; Humberto Sampaio Araújo (Revista Ciência Agronômica, 2023)
ABSTRACT The aim of this study was to evaluate agronomic performance in cultivars of the Cavendish banana under the soil and climate conditions of the microregion of Assis in the state of São Paulo over three production cycles. The experiment was set up at the Fazenda São José Farm, Água do Pau d´Alho, in Palmital, São Paulo. The Grande Naine, IAC2001 and FHIA02 cultivars were evaluated, considering the following variables: cultivar; plant height; pseudostem perimeter; number of leaves at flowering and harvest; number of days from planting to flowering, from planting to harvest, and from flowering to harvest; weight of the bunch, stalk and fruit per bunch; number of hands per bunch; productivity of the fruit and pulp; weight and number of fingers on the second hand; weight, length and diameter of the finger; pulp diameter; and weight and thickness of the peel. The data were subjected to multivariate statistical techniques (principal component factor analysis, tree clustering, two-way joining, and correspondence). The results showed the extraction of three principal factors that accounted for 89.63% of the total variance of the characteristics under analysis: banana production (Factor 1), vegetative development (Factor 2), and cultivars and fruit diameter (Factor 3). The productive performance of the FHIA02 cultivar was homogeneous and inferior to that of the other cultivars, as seen in the two-way joining cluster analysis. Only the Grande Naine and IAC2001 cultivars are recommended for cultivation in the micro-region of Assis, São Paulo, with Grande Naine showing the largest fruit and, especially, the largest pulp diameter.